Abnormal﻿ composition of microbiota in the gut and skin of imiquimod-treated mice - Hiroyo Shinno-Hashimoto (Nature Portfolio, 2021)
Abstract Psoriasis is a chronic, inflammatory skin disease. Although the precise etiology of psoriasis remains unclear, gut–microbiota axis might play a role in the pathogenesis of the disease. Here we investigated whether the composition of microbiota in the intestine and skin is altered in the imiquimod (IMQ)-treated mouse model of psoriasis. Topical application of IMQ to back skin caused significant changes in the composition of microbiota in the intestine and skin of IMQ-treated mice compared to control mice. The LEfSe algorithm identified the species Staphylococcus lentus as potential skin microbial marker for IMQ group. Furthermore, there were correlations for several microbes between the intestine and skin, suggesting a role of skin–gut–microbiota in IMQ-treated mice. Levels of succinic acid and lactic acid in feces from IMQ-treated mice were significantly higher than control mice. Moreover, the predictive functional analysis of the microbiota in the intestine and skin showed that IMQ caused alterations in several KEGG pathways. In conclusion, the current data indicated that topical application with IMQ to skin alters the composition of the microbiota in the gut and skin of host. It is likely that skin–gut microbiota axis plays a role in pathogenesis of psoriasis.